Effectiveness The Cooperative Problem Based Learning (CPBL) and Learning Motivation on Mathematical Literacy Abilities and Collaboration Skills - Mutrofin, Lika; Muhajir, Muhajir; Wahyuningtyas, Sri (UNDIKMA, 2024)
This type of research is quantitative research using a quasi-experimental design. The research method is conducted using a 3 x 2 factorial design since there are two independent variables. The research sample of 87 students was taken by random sampling technique from MTs Unggulan Amanatul Ummah Surabaya. The aims of the study were to test differences in mathematical literacy abilities and collaboration skills based on learning motivation levels and learning models. Data collection techniques using pretest, posttest, questionnaires and observation. Data analysis used a two-way ANOVA statistical test with SPSS software. The results showed that F result > F table and the probability value (Sig.) < ∝ = 0,05. It means that there were differences in mathematical literacy abilities and collaboration skills based on the level of learning motivation and learning models.